Research note: Laboratory study of the influence of changing the injection rate on the geometry of the fluid front and on P-wave ultrasonic velocities in sandstone - Lopes, Sofia; Lebedev, Maxim (Wiley-Blackwell Publishing Ltd., 2012)
Forced imbibition was performed in reservoir sandstone by injecting water into a dry sample. The injection was monitored with X-ray computed tomography and acoustic acquisition to simultaneously visualize the displacement of the fluid and quantify its presence by calculating saturation and P-wave velocities. We observed a strong influence when changing the injection rates on the acoustic response. Upon decreasing the injection rate from 5 mL/h to 0.1 mL/h, P-wave velocities decreased sharply: 100 m/s in 1 h. This behaviour is related to the partially saturated conditions of the sample (76% of saturation) before decreasing the injection rate. The air that is still trapped is free to move due to a decrease of pore pressure that is no longer forced by the higher injection rate. After 1 hour, P-wave velocities started increasing with small changes in saturation. Stopping injection for 16 hrs decreased saturation by 8% and P-wave velocities by 100 m/s. Restarting injection at 5 mL/h increased saturation to 76% while P-wave velocities fluctuated considerably for 2 hrs until they stabilized at 2253 m/s. Through the computed tomography scans we observed a water front advancing through the sample and how its shape changed from a plane to a curve after decreasing the injection rate.